Linking Profit Margin, Seo, and Roe: A Case of Uzbek Insurance Companies - Abdurasulov Behzodbek Bahodir ughli (Scientific Trends, 2023)
In this article, based on the financial reports of the participants of the insurance market of Uzbekistan, the relationship between their financial indicators, in particular, the relationship between the return on capital, profitability, insurance reserve, is studied. As a control factor, the impact of companies' online search engine optimization (SEO) on financial performance was also assessed. Also, in the article, these relationships were statistically analyzed using two different models
Keywords: Return on capital, profitability, SEO, insurance reserve, marketing, periodic costs, multifactor regression, logit model, marginal effects.